Simulasi Komputer Dalam Analisis Pergerakan Fluida - Dafa, Muhammad; Labik , Faizin (Lembaga Publikasi Ilmiah Nusantara, 2025)
Computer simulations have become a highly important tool in the analysis of fluid motion, particularly in the fields of engineering and science. With advancements in computational technology, numerical methods such as Computational Fluid Dynamics (CFD) are increasingly used to accurately model various fluid flow phenomena. This study aims to analyze the effectiveness of computer simulations in understanding fluid dynamics, both in laminar and turbulent flows. The methods employed include the application of numerical algorithms, geometry modeling, and the analysis of physical parameters that influence fluid movement. The simulation results indicate that computer-based approaches can represent flow characteristics with a high level of accuracy, especially under complex boundary conditions. Moreover, simulations allow for cost and time savings compared to physical experiments and offer flexibility in testing various system variables. The conclusion of this research affirms that computer simulation is an effective method for analyzing fluid motion and holds great potential for technological development across various fields, including mechanical engineering, aerospace, and the energy industry.